Framing Stereotypes: Patriarchic Perceptions in Malayalam Films - K. Karnamaharajan and Sherin V. Raj (Journal of Global Communication, 2010)
Film is a powerful medium which has a phenomenal impact on the audience. Since its reach and impact are unparallel, the characters played in a film and the message conveyed becomes very important for society. Also, to maintain the equilibrium in society, portrayal of women is of utmost important. This is despite the fact that the role of a hero will be given more thrust than his co-actor or any other characters in the film. But the Kerala society serves as a benchmark for several indicators and a role model for the rest of the country. The place is known for its highest literacy rate, and a positive sex ratio among the states in India. Also, it is a matrilineal society, a practice unique to Kerala where the property is inherited by the daughter and not by the son. Barring all the above mentioned facts, one would be shocked to review the films produced in such a progressive society. It is interesting to know whether the films made by the leading film producers are any different from those in the other parts of the country.